Saiva reformation of 19th century jaffna and the double kitchen tradition - Ahilan, P. (Lanka Decorative Arts, 2016)
Food choices, preparation methods, who prepares for whom, when and where, how the food should be displayed, what day and time it should be eaten and with whom, and how, are not simple, linear, social articulations. Rather, they are deeply imbricated in ethnicity, gender, caste, class and religion. As a result, food and practices of food preparation and consumption have become very contested, political issues within society. The discourse of vegetarianism was central to 'Neo Saivism' that was popularised among Hindus in the Indian sub-continent, during British colonial rule. 'Neo Saivism' in Jaffna was spear headed by Arumuga Navalar (1822-1879), a strong activist of Saiva reformation through education, preaching, writing and the publication of ancient religious chronicles that strongly condemned the consumption of non- vegetarian food. According to Navalar, eating non-vegetarian food polluted the pure Saivite body and anybody eating such foods would be consigned to hell. He described non-veg eaters as 'killers' and accused them of using their stomachs as a 'burial ground for animals.’ At the same time, Christian missionaries were questioning vegetarianism and Navalar's Saiva reformation movement in terms of its historical reliability. Rev. S. Gnana Pirakasar OMI 's book Neo Saivism extensively discussed the issue of vegetarianism. Similarly, the book The Tamils: Their early history and religion pointed out that Tamils had consumed non-vegetarian foods in ancient times. These debates pushed a certain number of Saivites to become vegetarians 25 while other Saivites sought to set up clear boundaries between vegetarian and non vegetarian practices. For example, Friday was established as an auspicious day on which Saivites would not consume non-vegetarian food. These debates also resulted in the innovation of the 'double kitchen' in colonial Jaffna -especially during the late 19th century and early 20th century. This type of 'double kitchen' is visible in certain parts of the Jaffna peninsula even today. While the function and practice of the 'double kitchen' has changed over the years, the boundary between vegetarian and non-vegetarian food still exists and continues to influence kitchen usage and culinary traditions.